Prangos multicostata (Apiaceae), a new species from eastern Kazakhstan - Lyskov, Dmitry F.; Kljuykov, Eugene V.; Samigullin, Tahir H.; Ukrainskaja, Uliana A.; Khrustaleva, Irina A. (Phytotaxa, 2016)
Prangos multicostata (Apiaceae) is described and illustrated as a new species from the Western Tarbagatai Mts. in Eastern Kazakhstan. The species is related to P. ledebourii, P. dzhungarica and P. herderi, but differs from the aforementioned taxa in the length of its leaflets, the absence of bracts and bracteoles, and the appearance of secondary ribs on the mericarps.